Pengembangan Sistem Forum Komunitas Sepeda berbasis Android - Yudha Pratama Nursam; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
There have been many bicycle communities that have sprung up in Indonesia. Every community has its own way of communicating. Smartphones and social media were chosen as communication tools that are widely used by community members as a forum for communicating, exchanging information and ideas. However, of the many social media that have been developed, there are problems that arise in their use, such as incomplete and inaccurate information obtained by community members. This is due to the mixing between knowledge information and communication information. In addition, there is no social media available on the Android platform which specifically only discusses the topic of bicycles. To overcome this, an Android-based bicycle community forum system was developed, with main features, such as community creation and post creation. Rapid Application Development was chosen as the method used in this research because it is able to accelerate system development and provide product results in accordance with stakeholder needs. System testing is carried out using white box testing and black box testing techniques. Each technique shows good results, in the form of input-out flow of three function program code verified correctly, and the entire system functionality is stated as one hundred percent valid, which means no failed functionality..